Stent Revascularization Restores Cortical Blood Flow and Reverses Tissue Hypoxia in Atherosclerotic Renal Artery Stenosis, But Fails To Reverse Inflammatory Pathways or GFR - Saad, Ahmed (2013)
BACKGROUND: Atherosclerotic renal artery stenosis (ARAS) is known to reduce renal blood flow (RBF), glomerular filtration rate (GFR) and amplify kidney hypoxia, but the relationships between these factors and tubulo-interstitial injury in the post-stenotic kidney are poorly understood. The purpose of this study was to examine the effect of renal revascularization in ARAS on renal tissue hypoxia and renal injury. METHODS AND RESULTS: Inpatient studies performed in ARAS patients (n = 17), more than 60% occlusion) before and 3 months after stent revascularization, or patients with essential hypertension (EH) (n = 32), during fixed Na+ intake and ACE/ARB Rx. Single-kidney (SK) cortical, medullary perfusion and RBF measured using multidetector CT, and GFR by iothalamate clearance. Tissue deoxyhemoglobin levels (R2*) measured by Blood Oxygen Level Dependent (BOLD) MRI at 3T, as was fractional kidney hypoxia (% of axial area with R2* > 30/s). In addition, we measured renal vein levels of Neutrophil gelatinase-associated lipocalin (NGAL), monocyte chemotactic protein-1 (MCP-1) and Tumor necrosis factor (TNF-α). Pre-stent SK-RBF, perfusion, and GFR were reduced in the post-stenotic kidney. Renal vein NGAL, TNF-α, MCP-1 and fractional hypoxia were higher in untreated ARAS than EH. After stent revascularization, fractional hypoxia fell (p < 0.002) with increased cortical perfusion and blood flow, while GFR and NGAL, MCP-1 and TNF-α remained unchanged. CONCLUSIONS: These data demonstrate that despite reversal of renal hypoxia and partial restoration of RBF after revascularization, inflammatory cytokines and injury biomarkers remained elevated and GFR failed to recover in ARAS. Restoration of vessel patency alone failed to reverse tubulointerstitial damage and partly explains the limited clinical benefit of renal stenting. These results identify potential therapeutic targets for recovery of kidney function in renovascular disease.